Mass-movements on the continental slope offshore Lofoten, Northern Norway - Baeten, Nicole Jeanne (Universitetet i Tromsø, 2013)
The papers of this thesis are not available in Munin: 1. Nicole J. Baeten, Jan Sverre Laberg, Matthias Forwick, Tore O. Vorren, Maarten Vanneste, Carl Fredrik Forsberg, Tore J. Kvalstad, Michael Ivanov: 'Morphology and origin of smaller-scale mass movements on the continental slope off northern Norway', Geomorphology(2013), vol.187:122-134, available at http://dx.doi.org/10.1016/j.geomorph.2013.01.008 2. Nicole J. Baeten, Jan Sverre Laberg, Matthias Forwick, Tore O. Vorren, Maarten Vanneste, Carl Fredrik Forsberg, Tore J. Kvalstad, Haflidi Haflidason: 'Origin of shallow submarine mass movements and their glide plane - sedimentological and geotechnical analyses from the continental slope off northern Norway' (manuscript) 3. Nicole J. Baeten, Jan Sverre Laberg, Matthias Forwick, Tore O. Vorren, Maarten Vanneste, Carl Fredrik Forsberg: 'Neogene - Quaternary contourite-drift growth and mass-movement activity on the continental slope offshore Lofoten, northern Norway'(manuscript) Swath bathymetry, side-scan sonar, sub-bottom profiler and seismic data from the continental slope offshore the Lofoten Islands, northern Norway reveal smaller-scale mass movements in water depths between 1100 and 2500 m. These mass movements have volumes of 0.061 to 8.7 km3 and are interpreted as translational slides involving spreading and multi-phase retrogression. The spatial variation in failure style is inferred to have been caused by the activation of different glideplanes (12.5-130 mbsf) within the thicker and more mounded contouritic deposits in the north-east of the study area. Data from a sediment core show that the shallowest style of mass movement (12.5 mbsf), was initiated within contouritic sediments characterized by high sensitivities and water contents. This unit overlies a plumite interval characterized by dilative behavior with pore pressure decrease with increasing shear strain and high undrained shear strength. As such, it is the difference in geotechnical properties which indicates that the interface between these ...